Digital Dance for People With Parkinson's Disease During the COVID-19 Pandemic: A Feasibility Study - Walton, Lois; Domellöf, Magdalena Eriksson; Åström, Åsa N.; Elowson, Åsa; Neely, Anna Stigsdotter (Frontiers in Neurology, 2022)
Background: Dance as a treatment to support physical, cognitive and emotional functioning, has gained increased acceptance as a healthcare intervention for people with Parkinson’s Disease (PD). The impact of the COVID-19 pandemic has been far reaching with devastating effects for at-risk populations. To find alternative and safe treatment delivery options during the pandemic has been of utmost importance. The purpose of this mixed-methods study was to evaluate the feasibility and the experience of digital dance for people with PD (Dance for PD©) and to examine change in self-reported quality of life, psychological health, subjective cognitive complaints and mental fatigue. Methods: 23 participants with PD (mean age 70) partook in ten one-hour weekly digital Dance for PD sessions. Feasibility outcome measures were assessed at post-test. Web-based questionnaires examining quality of life, subjective memory complaints, depression, anxiety and mental fatigue were administered at pre- and post-test. Moreover, nine participants partook in focus group discussions at post-test. Results: The results showed an acceptable feasibility to home-based digital Dance for PD, where 86% of the dance classes were completed, only minor negative side effects were reported (i.e. sore joints), and all experienced the dance classes as motivating and safe to do at home. The majority also reported positive effects on mood and physical functioning. The results from the questionnaires showed significant improvements in depressive symptoms (p = .006) and quality of life (p < .001) at post-test. In the focus groups, participants indicated that digital dance was a beneficial and enjoyable activity with a strong added value during the COVID-19 pandemic. Nevertheless, they experienced that digital dance missed some important elements of live dance. Conclusions: This study showed that digital Dance for PD is feasible and holds promise as a viable and safe method to keep people with PD dancing even when physical meetings are not possible. Beyond the pandemic, digital dance could be applied to a wide variety of patient groups including rural populations and patients for whom transportation may not be feasible for practical or financial reasons.